Peran Strategi Digital Perbankan Syariah Dalam Mendukung Perkembangan Ekonomi dan Ketahanan Menghadapi Tantangan Fintech - Dini Anggraini; Putri Wahyuni; Khaidar rahmaini jamila (CV. ITTC INDONESIA, 2026)
The development of digital technology has driven significant transformation in the banking industry, including Islamic banking. Digitalization is an important strategy for Islamic banking to improve service efficiency, expand financial inclusion, and maintain competitiveness amid the rapid growth of financial technology (fintech). This study aims to analyze the implementation of digitalization in Islamic banking, examine the role of Islamic banking digital strategies in supporting economic development, and assess the resilience of Islamic banking in facing fintech challenges. The research method used is a qualitative approach with a type of library research, through collecting and analyzing data from books, scientific journals, laws and regulations, and official publications of related institutions. The results show that the digital strategy of Islamic banking contributes positively to increasing financial inclusion, empowering MSMEs, operational efficiency, and Islamic economic growth. In addition, strategic collaboration between Islamic banking and fintech, supported by regulatory strengthening, digital risk management, and compliance with sharia principles, is key in maintaining the resilience of Islamic banking in the digital era.